Structure and Magnetic Properties of Y3−xErxFe5O12 (x=0.2,1.0, and 2.0) Thin Films Prepared by Sol-Gel Method - Ramadan Shaiboub; Noor Baa'yah Ibrahim; Mustaffa Abdullah; Ftema Abdulhade (Journal of Nanotechnology)
Nanoparticles Y3−xErxFe5O12 (x=0.2, 1.0, and 2.0) thin films were prepared by sol-gel method and treated at 800, 900, and 1000∘C, respectively, for 2 h. The films have single phase garnet structure and the sizes of particles are in the range of 44 to 83 nm. The magnetic measurements show that the saturation magnetization decreased with increasing of Er concentration for all samples treated at different annealing temperatures. The saturation magnetization increased with the particle size due to the enhancement of the surface spin effect. The coercivity initially decreased for x=1.0 and then increased for x=2.0 with increasing annealing temperature.